On the Ontology of Law and the Oblivion of Being - Šerpytytė, Rita (Religija ir kultūra, 2018)
This article hypothetically puts forth the idea of the ontology of Law as the “First Philosophy”. The presentation and justification of this idea is linked with the rethinking of the approach to examining law. This approach seeks to investigate law neither as the object of jurisprudence, legal theory, nor even, and this is especially crucial, legal philosophy; it rather consists in justifying the possibility of looking at the law from an ontological philosophical perspective, revealing the fundamental link between law and being. In contrast, by treating law as a given and not raising the question of its emergence as such, by searching for “right” laws “in accordance with nature”, even when ontological terms are being used, the ontological context of law’s emergence is not revealed; rather, only ontological pretentions to existing laws are asserted. This article discusses the work of the Ancient philosophy scholar Werner Jaeger, which allows one to rethink the idea of the ontology of law and to outline the direction for “resetting” the notion of law.